APLIKASI GAME PUZZLE HURUF HIJAHIYAH UNTUK ANAK-ANAK BERBASIS ANDROID - Ananda Faridhatul Ulva; Chairul Akbar (JTIK (Jurnal Teknik Informatika Kaputama), 2021)
Mobile device technology is growing rapidly, especially with the emergence of smartphones with the Android operating system. Users in this case can download various basic applications available easily on the google play store. But most of them are available in less educational game form. In fact, it often has negative consequences for users, especially for children who are still unable to distinguish positive and negative. Early childhood education stages tend to be interested in games that are easy to play and have an attractive visual appearance with a variety of colors and varied images that attract attention. This stage will also make it easier to remember the lesson. Therefore, researchers made a puzzle game application that can provide entertainment and education to users, especially children. This android based hijaiyah letter puzzle game application was built using Construct 2 converted with Phonegap into an Apk file. The application of this application is by installing a puzzle game application on a smartphone with the specifications of the Android operating system version 5.1+ (lollipop).